COVID‐19 and vertical transmission: assessing the expression of ACE2/TMPRSS2 in the human fetus and placenta to assess the risk of SARS‐CoV‐2 infection. (18th November 2021) - Beesley, MA; Davidson, JR; Panariello, F; Shibuya, S; Scaglioni, D; Jones, BC; Maksym, K; Ogunbiyi, O; Sebire, NJ; Cacchiarelli, D; David, AL; De Coppi, P; et al.
Abstract : Background: Pregnant women have been identified as a potentially at‐risk group concerning COVID‐19 infection, but little is known regarding the susceptibility of the fetus to infection. Co‐expression of ACE2 and TMPRSS2 has been identified as a prerequisite for infection, and expression across different tissues is known to vary between children and adults. However, the expression of these proteins in the fetus is unknown. Methods: We performed a retrospective analysis of a single cell data repository. The data were then validated at both gene and protein level by performing RT‐qPCR and two‐colour immunohistochemistry on a library of second‐trimester human fetal tissues. Findings: TMPRSS2 is present at both gene and protein level in the predominantly epithelial fetal tissues analysed. ACE2 is present at significant levels only in the fetal intestine and kidney, and is not expressed in the fetal lung. The placenta also does not co‐express the two proteins across the second trimester or at term. Interpretation: This dataset indicates that the lungs are unlikely to be a viable route of SARS‐CoV2 fetal infection. The fetal kidney, despite presenting both the proteins required for the infection, is anatomically protected from the exposure to the virus. However, the gastrointestinal tract is likely to be susceptible to infection due to its high co‐expression of both proteins, as well as its exposure to potentially infected amniotic fluid. Tweetable abstract: This work provides detailed mechanistic insight into the relative protection & vulnerabilities of the fetus & placenta to SARS‐CoV‐2 infection by scRNAseq & protein expression analysis for ACE2 & TMPRSS2. The findings help to explain the low rate of vertical transmission. Tweetable abstract: This work provides detailed mechanistic insight into the relative protection & vulnerabilities of the fetus & placenta to SARS‐CoV‐2 infection by scRNAseq & protein expression analysis for ACE2 & TMPRSS2. The findings help to explain the low rate of vertical transmission.